The Integration of Metabolomics and Next-Generation Sequencing Data to Elucidate the Pathways of Natural Product Metabolism in Medicinal Plants - Scossa, Federico; Benina, Maria; Alseekh, Saleh; Zhang, Youjun; Fernie, Alisdair R. (Planta Medica, 2018)
Plants have always been used as medicines since ancient times to treat diseases. The knowledge around the active components of herbal preparations has remained nevertheless fragmentary: the biosynthetic pathways of many secondary metabolites of pharmacological importance have been clarified only in a few species, while the chemodiversity present in many medicinal plants has remained largely unexplored. Despite the advancements of synthetic biology for production of medicinal compounds in heterologous hosts, the native plant species are often the most reliable and economic source for their production. It thus becomes fundamental to investigate the metabolic composition of medicinal plants to characterize their natural metabolic diversity and to define the biosynthetic routes in planta of important compounds to develop strategies to further increase their content. We present here a number of case studies for selected classes of secondary metabolites and we review their health benefits and the historical developments in their structural elucidation and characterization of biosynthetic genes. We cover the cases of benzoisoquinoline and monoterpenoid indole alkaloids, cannabinoids, caffeine, ginsenosides, withanolides, artemisinin, and taxol; we show how the “early” biochemical or the more recent integrative approaches–based on omics-analyses–have helped to elucidate their metabolic pathways and cellular compartmentation. We also summarize how the knowledge generated about their biosynthesis has been used to develop metabolic engineering strategies in heterologous and native hosts. We conclude that following the advent of novel, high-throughput and cost-effective analytical technologies, the secondary metabolism of medicinal plants can now be examined under the lens of systems biology.
Keywords: Papaver somniferum; Papaveraceae; Catharanthus roseus; Apocynaceae; alkaloids; caffeine; cannabinoids; ginseng; artemisinin; taxol